The Effect of Application of Sonic Vibration on the Bond Strength of Glass Fiber Post to Root Dentin using Duo-link and Theracem cements: An In Vitro Study - Maryam Hoseini; Mohammad Reza Malekipour; Farzaneh Shirani (Wolters Kluwer Medknow Publications, 2022)
Background: This study investigated the impact of sonic vibration on the root dentin-glass fiber post bond strength using two resin cements. Materials and methods: Forty single-canal teeth were randomly divided into four groups (n = 10): Theracem self-adhesive using sonic vibration, Duo-link cement using sonic vibration and abrasion, Theracem self-adhesive, and Duo-link cement. Data were analyzed by one-way analysis of variance, Tukey test, and independent t test (α = 0.05). Results: In the coronal region, the bond strength was not significantly different among the four groups (P = 0.331). In the apical region, the bond strength was significantly higher in the Duo-link cement using sonic vibration than in the Theracem cement using sonic vibration (P = 0.010) and Theracem cement using the conventional method (P = 0.007). Conclusion: Sonic vibration has positively affects the push-out bond strength of glass fiber post to root dentin using Duo-link cement.